Latihan Fisik terhadap Penurunan Cancer Related Fatigue pada Pasien Kanker Payudara - Linda Jurwita; Dewi Elizadiani Suza; Mula Tarigan (Journal of Telenursing (JOTING), 2021)
This study aims to identify and evaluate the effect of a physical exercise intervention on reducing cancer-related fatigue in breast cancer patients. The method used is Systematic Reviews using EBSCO, PubMed and ProQuest databases. The articles were selected using the PRISMA (Preferred Items for Systematic Reviews and Meta-Analyses) diagram, which found ten articles that matched the inclusion criteria. The results showed that physical exercise had a significant effect on reducing fatigue and could improve the quality of life of breast cancer patients. In conclusion, physical exercise intervention can help relieve symptoms and reduce cancer-related fatigue in breast cancer patients. Keywords: Cancer Related Fatigue, Breast Cancer, Physical Exercise